1985
DOI: 10.1093/nar/13.17.6343
|View full text |Cite
|
Sign up to set email alerts
|

Specific ribosomal RNA recognition by a fragment ofE. coliribosomal protein S4 missing the C-terminal 36 amino acid residues

Abstract: We have previously investigated the role of the N-terminal region of ribosomal protein S4 to participate in 30S ribosome assembly and function (1-3). In this report we extend these studies to the two fragments produced by the chemical cleavage of protein S4 at the tryptophan residue 167. We find that the carboxyl terminal fragment (168-203) does not bind 16S RNA nor does it participate in assembly with the other 20 proteins from the 30S ribosome. In contrast, the larger fragment (1-167), does bind 16S RNA spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Fragments terminating at residues 171, 119 and 101 ( B.stearothermophilus numbering) were also made. All retained some affinity for rRNA (Changchien and Craven, 1985, 1986; Conrad and Craven, 1987). However, later studies using circular dichroism showed that any truncation of the molecule prior to residue 171 resulted in a marked destabilization (Baker and Draper, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Fragments terminating at residues 171, 119 and 101 ( B.stearothermophilus numbering) were also made. All retained some affinity for rRNA (Changchien and Craven, 1985, 1986; Conrad and Craven, 1987). However, later studies using circular dichroism showed that any truncation of the molecule prior to residue 171 resulted in a marked destabilization (Baker and Draper, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…S4 fragments with C-terminal deletions produced by Me 2 SOHBr reaction with Trp-170, hydroxylamine cleavage at Asn-123/Gly-124, or cyanogen bromide reaction at Met-105 have been described (14,15,41). All of these interact preferentially with 16 S rRNA over 23 S rRNA in an assay in which the binding of labeled protein to nitrocellulose filters is prevented by formation of the protein-RNA complex (42).…”
Section: Mrna Binding Of Ribosomal Protein S4 Fragmentsmentioning
confidence: 99%
“…In this paper we build on the previous work of Craven and colleagues (12)(13)(14)(15), who cleaved S4 by various methods and studied the ability of the protein fragments to bind 16 S rRNA and promote ribosome assembly in vitro. We have prepared a number of similarly truncated proteins by overexpression of the S4 gene rather than cleavage methods, and show that Nand C-terminal regions of S4 that are not necessary for rRNA binding are also not required for S4 recognition of the ␣ mRNA pseudoknot.…”
mentioning
confidence: 99%
“…We have determined that the N-terminal 46 amino acids of S4 are not required for S4 binding to 16S RNA, although residues 31-46 are involved in assembly (6). We have also shown that residues 168-203 are not involved in rRNA binding (7); they seem however to be involved in conformational changes in assembly and in the translational repression of the S4 operon (8,9). The smallest active fragment of S4 that we have generated so far consisted of residues 1-124 and was produced by hydroxylamine cleavage (10).…”
mentioning
confidence: 90%
“…We report here the production of a fragment of S4 consisting of residues 1-103, generated by cyanogen bromide (CNBr) cleavage, which rebinds 16S RNA with an affinity comparable to intact S4. However, this loss of almost half of the protein has severely affected its ability to participate in 30S assembly, not so much in terms of protein incorporation, but in a conformational contraction proposed to take place at a late stage in assembly (7).…”
mentioning
confidence: 99%